THE IMPLICATION OF THE TEACHING OF THORIKOH QODIRIYAH WA NAQSABANDIYYA DARUL FALAH MATARAM ON FAMILY HARMONY - Abdul Malik; Sainun; Muhasim (Familia: Jurnal Hukum Keluarga, 2025)
This study concerns the teachings of Thoriqoh Qodiriyah wa Naqsabandiyah (TQN) Darul Falah Mataram and their implications for marital harmony among followers. Indonesia's divorce rate reached 466,000 cases in 2023 (BPS, 2023), indicating the need for alternative approaches to strengthen family institutions. This qualitative case study was conducted in Pagutan Village, Mataram City, NTB, employing triangulation through in-depth interviews with Mursyid, Khalifah, and 15 followers (selected purposively based on marriage duration >5 years and active participation >3 years), participant observation, and documentation. Data analysis utilized descriptive techniques following Miles and Huberman's model. Results show TQN's three pillars dhikr, muraqaba, and Tafakkur practiced through structured activities significantly improve marital harmony through: (1) enhanced interpersonal communication quality (openness, empathy); (2) moral character development (patience, compassion); and (3) strengthened family solidarity. Duck's Interpersonal Communication Theory and Pargament's Spiritual Theory validate these findings. The tariqa community functions as emotional support, spiritual identity formation, and constructive conflict resolution, contributing to harmonious households based on Mawaddah wa Rahmah principles (QS Ar-Rum:21). This research fills the literature gap on tariqa's role in family harmony and offers practical insights for spiritual-based household guidance strategies aligned with Islamic Family Law principles.